The impact of practical learning on improving students' Arabic speaking skills: the International Islamic University Malaysia as a case study - Chtaibi, Khalid; Nasirudeen, Abdulwasiu; M., Farheen Mufid (Al-Madinah International University (MEDIU) Malaysia, 2026)
The article contributes to the understanding of the practical learning process in developing students’ linguistic skills an d abilities when they embark upon the study of the Arabic language. This research aims to identify the impact of practical learning and to determine the benefits of studying Arabic beyond the theoretical aspects. The study employed a quantitative methodology, utilizing a questionnaire completed by 50 students pursuing Arabic for international communication in Kulliyyah of Sustainable Tourism and Contemporary Languages. Most respondents indicated that practical learning facilitates the enhancement of their oral proficiency. In their own learning style, the students apply themselves to the development of their speaking abilities and skills in the Arabic language. Practical learning within the context of the Arabic course cannot facilitate the understanding of Arabic native speaker language for those who have not yet acquired sufficient fluency, particularly in the case of beginners. The result from this research showed that students who majored in Arabic for international communication indicated that practical learning helped them develop their talents and skills in the Arabic language, acquiring skills through practical learning has a clear positive impact on mastering verbal communication, especially in the areas of clarity of ideas and strategic communication and lastly, practical learning represents a complementary appro ach to traditional education, effectively co mplementing theoretical knowledge with practical experience to enhance the development of speaking talents and skills.